Brand revitalization creating a plan to win - Light, Larry (Pearson Education Pub. as FTPress Delivers, 2010)
"This Element is an excerpt from Six rules for brand revitalization: learn how companies like McDonald's can re-energize their brands (ISBN: 9780136043317) by Larry Light and Joan Kiddon. Build a systematic Plan to Win for revitalizing your brand: stop playing "not to lose," and get your entire organization aligned for the win!"--Resource description page.
Keywords: Branding (Marketing) -- Management; Brand name products -- Management; Product life cycle; Stratégie de marque; Gestion; Produits de marque; Gestion; Produits commerciaux; Cycle de vie; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Branding (Marketing); Management; Brand name products; Management